MUTU TERPADU PADA PENDIDKAN ANAK USIA DINI ISLAM (PAUDI) - Miki Sandi; Santy Santy; Rhendica Rhendica (Jurnal Manajemen Pendidikan, 2026)
Objective: The quality of education in Islamic Early Childhood Education (PAUDI)becomes very urgent because it plays a role in optimizing children's developmentduring the golden period in cognitive, socio-emotional, and spiritual aspects.However, there are issues such as limited human resources, high administrativeburdens, low understanding of the quality assurance system, and the suboptimalintegration of Islamic values in institution management. This study aims tocomprehensively examine the concept and implementation of integrated quality inPAUDI.Methods: The method used is a literature study with a descriptive-analyticalqualitative approach through tracking sources from national journals, regulatorydocuments, and related policies over the last 10 years. The analysis technique usescontent analysis with data grouping based on early childhood education standards,independent curriculum, and indicators of holistic child development.Results:Demonstrating that integrated quality in PAUDI requires the integration ofeducation standards based on the Ministry of Religious Affairs, the implementation ofa child-centered independent curriculum, quality measurement based on the holisticdevelopment of children as caliphs, as well as strengthening governance through aSchool Based Management approach that is integrated with Islamic values.Novelty: The development of a quality management information system (SIM-SPMI)has become an important strategy in improving the effectiveness of institutionalmanagement. In conclusion, the implementation of integrated quality in PAUDIrequires an integrative, systematic, and sustainable approach, but there are still gapsin the aspects of practical implementation and contextual integration models in thefield.